Literature Study on the Influence of Transformational Leadership, Motivation, and Job Satisfaction on Employee Performance - Kironowati, Sabto; Yosepha, Sri Yanthy (Dinasti Publisher, 2025)
In the context of rapidly occurring globalization, human resources management has become critically important for achieving organisational success, enabling operations to be conducted more efficiently and productively. One of the primary challenges faced is the management of workforce diversity, which encompasses differences in gender, age, and educational background. Effective diversity management necessitates a fair and inclusive approach, ensuring that every individual can contribute to their fullest potential. Therefore, it is essential to integrate various backgrounds to enhance productivity and support the company's vision and mission. The main objective of this academic article is to reinforce existing theoretical foundations and to provide a detailed explanation of the phenomena related to the relationships or influences occurring between the variables under investigation. This article will specifically discuss and analyse various factors that affect employee performance, a critical aspect of human resource management. Through meticulous identification and a review of the existing literature, it has been discovered that: 1) Transformational Leadership has a significant impact on job satisfaction; 2) Motivation influences employee performance; 3) Job Satisfaction affects performance; and 4) Whether these three variables simultaneously influence performance. Relevant prior research serves as a reference point for the literature review in this academic article, thereby providing a basis for future research, particularly in the realm of human resource management.